Socially Inclusive In Palembang City Light Rail Transit (LRT) For The Development Of A Green Economy In A Sharia Economic Perspective - Yuliani, Mawar; Heri Junaidi; Deky Anwar (SEAN Institute, 2024)
The issues of sustainability and social inclusiveness are increasingly becoming a concern in the development of modern public transportation. Palembang City Light Rail Transit (LRT), as one of the based transportation projects green economy offers opportunities to apply concepts socially inclusive to achieve social justice and accessibility for all levels of society. From a sharia economic perspective, sustainable and inclusive transportation development does not only consider economic efficiency and environmental preservation, but also pays attention to fair and equitable social welfare. This research aims to explore the application of the concept socially inclusive on the Light Rail Transit (LRT) transportation system in Palembang City as part of development efforts green economy which is in line with sharia economic principles. This study also discusses how sharia economic principles—such as social justice, wise use of resources, and shared prosperity—can be integrated into LRT development policies to maximize positive social and economic impacts. This type of research is field research and is included in qualitative descriptive research using primary and secondary data. Data collection techniques use observation, interviews and documentation methods. The data analysis technique in this research uses data reduction, data presentation, and drawing conclusions. The research results show that overall it can be achieved triple bottom line (people, planet, profit) which means that the development of a green economy can be carried out through Socially Inclusive, because by fulfilling the Triple Bottom line concept, the Green Economy concept is also fulfilled. Green Economy Development Through the Quadruple Helix Approach on Light Rail Transit in Palembang City can only fulfill 1-3 indicators, namely the role of government, business actors and the community and sharia economic principles. It can also be implemented in socially inclusive and green economy development.